Cost Consequence Analysis of Antidiabetic Therapy in Covid-19 Hospitalized Patients with Diabetes Mellitus at Panembahan Senopati Hospital Yogyakarta - Fatimah, Fitri Andriani; ST. Mualifah; Hidayati, Listiana; Nilansari, Anis Febri (Pharmacon: Jurnal Farmasi Indonesia, 2024)
One of the significant respiratory infections is Covid-19, and its occurrence in Indonesia varies due to the diverse geographical positions across the region. Therefore, demographic groups consisting of individuals of a certain age and those with certain medical conditions remain at the highest risk of contracting Covid-19. The severity of Covid-19 patients are greatly influenced by underlying health conditions such as diabetes mellitus, hypertension, age, and obesity. In particular, diabetes mellitus is associated with an increased risk of severe illness and mortality among Covid-19 patients, potentially impacting healthcare expenditure, especially pharmaceutical costs. Therefore, this study aims to describe the financing of medication therapy, the outcomes of antidiabetic therapy, and the average direct medication costs inpatients with Covid-19 at Panembahan Senopati Hospital. Using a non-experimental descriptive-analytic approach, this study retrospectively collected data from medical records from 2020 to 2021. The results showed: 1) a description of diabetes mellitus treatment therapy with Covid- 19, namely the most common single therapy is the use of insulin, namely Novorapid and Novomix, a combination therapy of 2 drugs, namely Metformin + Novorapid, while a combination therapy of 3 drugs, namely Metformin + Novorapid + Glibenclamide 2) the achievement of therapeutic outcomes in diabetic patients with Covid-19 who received therapy as many as 77.27% of patients reached the target and 22.73% of patients had not reached the target glucose level 3) the average direct treatment cost of hospitalized diabetes mellitus patients with Covid-19 was IDR. 5,234,858 per patient based on the hospital's perspective.